Triptych : three into one = one - Cotton, Dan (Wooroloo, Western Australia : R.Ohm Estate, 2018)
Jack Collins was a happily married and successful Perth businessman. So why didn’t he return home after a routine interstate conference, and why hasn’t he been seen since? To find the answers, Jack’s tormented sister-in-law recruits an ex-cop with a dark history. What she gets is not what she expects. Perhaps the CCTV footage that shows her sister's husband coldly assassinating a Sydney crime boss might provide a clue, or it might not.
First published in 2016.
Keywords: Murder -- investigation -- Fiction; Corruption -- Fiction; Detective and mystery stories; Australian fiction; Perth (W.A.) -- Fiction; Australian